Evaluation of Scholarship Motivators and Barriers for Non-Tenure-Track Faculty in a Department of Pharmacy Practice - Cecilia Farias-Ruiz; Theresa Byrd; Eric J. MacLaughlin; Ronald G. Hall 2nd (Pharmacy, 2023)
The Accreditation Council for Pharmacy Education (ACPE) Standards 2016 set explicit expectations for faculty scholarship. However, many non-tenure-track faculty have struggled with the scholarship portion of the academic tripart mission of clinical practice, teaching, and scholarship. Therefore, we sought to identify themes regarding the barriers, motivators, and potential solutions associated with non-tenure-track faculty scholarship. Four focus group interviews were held via videoconference during July 2021, which consisted of non-tenure-track faculty within the TTUHSC Jerry H. Hodge School of Pharmacy. Each focus group answered a standard script of questions that were evaluated for face validity over a 30–60 min session. Twenty-two non-tenure-track faculty members (47% response) participated in one of the four focus group interviews. The four common barriers were insufficient time, lack of acknowledgment, obscurity of scholarship expectations, and a lack of resources and support. Scholarship’s lasting impact on academia, students, and clinical practice was the one common motivator identified by the groups. The barriers identified were not unique to our faculty, despite the unique four-city structure of our program. Actions have continued to be taken to help address the barriers and potential solutions identified by the focus groups. In summary, our results echo that non-tenure-track faculty need more time and training to help them feel like they can meet institutional scholarship requirements.